2021
DOI: 10.1002/rrq.385
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Simple View of Reading: The Role of Executive Functions in Emergent Bilinguals’ and English Monolinguals’ Reading Comprehension

Abstract: The simple view of reading describes reading as the product of decoding (D) and listening comprehension (LC). However, the simple view of reading has been challenged, and evidence has proved it to be too simple to explain the complexities of reading comprehension in the elementary school years. Hypotheses have been advanced that there are cognitive-linguistic factors that underlie the common variance between D and LC, which are malleable, although there is no clarity at this point regarding what these are. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 88 publications
(163 reference statements)
0
24
1
Order By: Relevance
“…As noted earlier, EF skills play a key behind-the-scenes role in helping readers achieve orthographic mapping, which involves links across elements of word recognition and language comprehension (Aboud et al, 2016(Aboud et al, , 2018Ehri, 2014;Perfetti & Stafura, 2014;Yu et al, 2018). Recent work has supported this notion, demonstrating that EF skills contribute to reading through a path from language comprehension to word recognition to reading (Cartwright, Lee, et al, 2020;Taboada Barber et al, 2021). Further, domain-general EF skills are amenable to intervention, which directly improves reading (e.g., Dahlin, 2011;Johann & Karbach, 2019;Loosli, Buschkuehl, Perrig, & Jaeggi, 2012).…”
Section: Domain-general Efmentioning
confidence: 87%
See 1 more Smart Citation
“…As noted earlier, EF skills play a key behind-the-scenes role in helping readers achieve orthographic mapping, which involves links across elements of word recognition and language comprehension (Aboud et al, 2016(Aboud et al, , 2018Ehri, 2014;Perfetti & Stafura, 2014;Yu et al, 2018). Recent work has supported this notion, demonstrating that EF skills contribute to reading through a path from language comprehension to word recognition to reading (Cartwright, Lee, et al, 2020;Taboada Barber et al, 2021). Further, domain-general EF skills are amenable to intervention, which directly improves reading (e.g., Dahlin, 2011;Johann & Karbach, 2019;Loosli, Buschkuehl, Perrig, & Jaeggi, 2012).…”
Section: Domain-general Efmentioning
confidence: 87%
“…The componential model's inclusion of motivation and ecological factors certainly extends it beyond the SVR. However, in our reading of the componential model, there is no component that addresses causes of reading disability beyond those within word recognition or language comprehension, the shared variance (i.e., overlap) between word reading and linguistic comprehension, or some self-regulation processes that contribute to and through that overlap, such as executive functioning (e.g., Taboada Barber et al, 2021).…”
Section: The Componential Model Of Readingmentioning
confidence: 99%
“…A handful of studies support the notion that decoding and language skills are the main components explaining the development of reading comprehension (Hjetland et al, 2019; Protopapas, Simos, Sideridis, & Mouzaki, 2012; Torppa et al, 2016). However, many scholars have questioned the simplicity of the SVR model, leading them to investigate the contribution of additional components to reading comprehension, for example, reading fluency (Adlof, Catts, & Little, 2006), prior knowledge (Taboada Barber, Cartwright, Hancock, & Klauda, 2021), and Executive function (EF) abilities (Butterfuss & Kendeou, 2018; Sesma, Mahone, Levine, Eason, & Cutting, 2009). The term EF refers to a set of higher‐level cognitive abilities that regulate learning processes (Demakis, 2004; Meltzer, 2018) and include inhibition, switching, speed of processing, and flexibility (Anderson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition is the ability to block irrelevant information from interfering with the task that is being completed (Miyake et al, 2000), such as disregarding distractions while reading so one can focus on relevant information in text. Of these core EF skills, WM and CF have consistently shown significant, unique contributions to reading comprehension beyond inhibition (e.g., Christopher et al, 2012; Taboada Barber et al, 2021); thus, we focused on WM and CF in the current study.…”
mentioning
confidence: 99%
“…Specifically, Lawson and Farah (2017) found that EF, as a latent construct, mediated the relation between SES and reading in a sample of 6‐ to 15‐year‐olds. The present study sought to move the literature forward by examining mediating roles of individual EF skills that have been demonstrated to be uniquely influential in the development of reading comprehension (e.g., Altemeier et al, 2008; Christopher et al, 2012; Nouwens et al, 2016; Taboada Barber et al, 2021) rather than considering EF as a single composite variable. Specifically, we explored how WM and CF mediate the relation between SES and reading achievement during the transition from kindergarten to first grade using data from Early Childhood Longitudinal Study, Kindergarten Class of 2010–2011 (ECLS‐K:2011), a nationally representative sample of students in the United States, allowing for broader inference than prior research.…”
mentioning
confidence: 99%